Fall flow reversals at Intermediate Waters in the Lanzarote Passage from nine-year record - Machín, F.; Fraile-Nuez, Eugenio; Pelegrí-Llopart, José Luis; López-Laatzen, Federico; Vélez-Belchí, Pedro; Hernández-Guerra, A. (Journal of Physical Oceanography, 2010)
Two 9-yr current-meter and salinity records, together with climatological data, reveal marked seasonal variability of the intermediate flow at a key location in the Canary Basin. The region is characterized by a summer (July–September) and early fall (October) northward progression of Antarctic Intermediate Water followed by a fall (November–December) intense flow reversal of Mediterranean Water. A Sverdrup-type model confirms that these movements are associated with stretching or shrinking of the intermediate water strata. Sí